HUBUNGAN DUKUNGAN SUAMI TERHADAP KECEMASAN PADA IBU HAMIL TRIMESTER III - Ummu Luthfiyah; Diana Rifka Yulia Wahyuni; Gustiyana Astiti (Ensiklopedia of Journal, 2025)
Pregnancy is a time of physical and psychological changes for a woman, especially in the third trimester which is a period of preparation for childbirth. During this period, pregnant women are more susceptible to psychological disorders such as stress and anxiety, which can affect the health of the mother and fetus. The role of the husband is very important in providing assistance during pregnancy. During the visit of pregnant women at the Sidomulyo Inpatient Health Center, Pekanbaru City in June-July 2024, there were 32 people. This study aims to determine the relationship between husband's anxiety and third trimester pregnant women at the Sidomulyo Inpatient Health Center, Pekanbaru City. This study uses a descriptive analytical design method with a cross-sectional approach with dependent and independent variables. The sample in this study was 32 third trimester pregnant women who came to the Sidomulyo Inpatient Health Center, the data collection instrument used a questionnaire, the data was tested with the chi square test at a significance level of 95% (p = 0.05). The results showed that there were 27 (84.38%) husbands who provided support and 5 (15.62%) who did not provide support. There were 26 (81.25%) who experienced anxiety and 6 (18.75%) who did not experience anxiety. The results of the ChiSquare analysis obtained a p value of 0.002 0.05 with a significance level of 5% (0.05). In this study, there was a relationship between husband's support and anxiety in facing childbirth in pregnant women in the third trimester at the Sidomulyo Inpatient Health Center, Pekanbaru City. This study suggests the importance of increasing husband involvement in providing support during pregnancy to reduce anxiety levels in pregnant women in the third trimester.Keywords: Third trimester pregnant women, husband’s support, anxiety